Overview of Nurses Factors about Safety Behavior of Infusting in the Emergency Room (ER) of Lumajang Regional Hospital - Dwi Ochta Pebriyanti (Universitas Bondowoso, 2022)
Introduction: Hospitals are unique and complex workplaces, with hospital workers who undergo more occupational health and safety problems than other civilian workers. Accident and Emergency Room (ER) is the main window in hospital services which is always related with the patient’s soul. The accident and emergency roomalso has a higher risk because it provides first aid to patients whose medical history is unknown. The study aimed to describe the nurses factors of safety behavior in infusion in the emergency room of Lumajang regional hospital. Method: This study used a qualitative method based on a descriptive survey. This study used a total sampling, with a total of 20 nurses as respondents. The data collection technique used a questionnaire in interviews and observation using a checklist sheet. Result: Indicated that most of them were male, with the working period between <5 years and> 5 years, most of them had never attended OSH training / socialization, and the last level of formal education was Diploma III of Nursing. Most of them had a level of knowledge. about OSH and work safety motivation in the high category, and 85% of nurses still had unsafe behavior in infusion during work. Conclusion: pointed out that nurses who had a safety behavior in the less safe category were nurses with a high level of knowledge about OSH and nurses with high motivation for work safety who had a safety behavior in the less safe category